A Holistic Approach to Upwelling and Downwelling along the South-West Coast of India. Issue 1 (2nd January 2019) - Shah, Phiros; Sajeev, R.; Thara, K. J.; George, Grinson; Shafeeque, Muhammad; Akash, S.; Platt, Trevor
Abstract: An attempt has been made to develop a holistic understanding of upwelling and downwelling along the south-west coast of India. The main objective was to elucidate the roles of different forcings involved in the vertical motion along this coast. The south-west coast of India was characterized by upwelling during the south-west monsoon (May to September) and by downwelling during the north-east monsoon and winter (November to February). The average vertical velocity calculated along the south-west coast from the vertical shift of the 26 °C isotherm is 0.57 m/day during upwelling and 0.698 m/day during downwelling. It was concluded that upwelling along the south-west coast of India is driven by offshore Ekman transport due to the alongshore wind, Ekman pumping, horizontal divergence of currents and by the propagation of coastally trapped waves. Whereas downwelling along the coast is driven only by convergence of currents and the propagation of coastally trapped Kelvin waves. Along the west coast of India, the downwelling-favorable Kelvin waves come from the equator and upwelling-favorable waves come from the Gulf of Mannar region.